2017
DOI: 10.1007/s40264-017-0605-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Russian-Backbone Trivalent, Live Attenuated Seasonal Influenza Vaccine in Healthy Subjects: Open-Label, Non-randomized Phase 4 Study

Abstract: Clinical Trials Registry of India (CTRI/2015/08/006074).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“… 146 Another intranasal live attenuated vaccine, Nasovac-S, has been approved in India, as its safety and efficacy were confirmed after administration to a large population. 147 …”
Section: Licensed In Vaccinesmentioning
confidence: 99%
“… 146 Another intranasal live attenuated vaccine, Nasovac-S, has been approved in India, as its safety and efficacy were confirmed after administration to a large population. 147 …”
Section: Licensed In Vaccinesmentioning
confidence: 99%
“…LAIVs based on Len/17-MDV or B/USSR/60/69 have been used for decades in Russia and since 2011 in India. Vaccines generated using these two backbones have been shown to be safe and effective [3], [4], [5], [6]. In some studies, superior efficacy of LAIV over inactivated vaccines has been observed for both antigenically well-matched and drifted viruses [7].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, reversion of an Ann Arbor-backbone LAIV (FluMist™) to a phenotype capable of inducing disease in mice following serial passage of the vaccine virus at increasing temperatures 58 highlights the need to consider alternative LAIV backbones for future LAIV formulations. Indeed, a Leningrad-based LAIV developed by the Institute of Experimental Medicine (Russia) and subsequently sublicensed via a World Health Organization influenza technology transfer initiative 59 has been demonstrated to be safe and well tolerated in human clinical trials 59 , 60 .…”
Section: Discussionmentioning
confidence: 99%